2021
DOI: 10.1017/s0022149x21000171
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum frutescens and Citrus limon: a new take on therapy against experimental trichinellosis

Abstract: Trichinellosis is a zoonotic disease that endangers human health and can lead to death. Restricted absorption and poor results of conventional therapies demand new effective natural remedies to treat both enteral and parenteral trichinellosis. This study assessed the antiparasitic and anti-inflammatory effects of Citrus limon and Capsicum frutescens on murine trichinellosis and compared them with those of albendazole and prednisolone, which are conventionally used to treat trichinellosis. Overall, 50 Swiss alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The effect of albendazole on T. spiralis larvae was lower than that its effect on adults due to the limited bioavailability of oral administration and water solubility of albendazole (Caner et al, 2008). These results are consistent with those of Salama et al (2021), who reported that the percentages of reduction in both total adult worm and muscle larval counts in the albendazole treated group were 93.5% and 90.6%, respectively. Moreover, Huang et al (2020) reported the high efficacy of albendazole on adult worms and its reduced efficacy on muscle larval counts at 97.7% and 49.1%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The effect of albendazole on T. spiralis larvae was lower than that its effect on adults due to the limited bioavailability of oral administration and water solubility of albendazole (Caner et al, 2008). These results are consistent with those of Salama et al (2021), who reported that the percentages of reduction in both total adult worm and muscle larval counts in the albendazole treated group were 93.5% and 90.6%, respectively. Moreover, Huang et al (2020) reported the high efficacy of albendazole on adult worms and its reduced efficacy on muscle larval counts at 97.7% and 49.1%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with those of Salama et al . (2021), who reported that the percentages of reduction in both total adult worm and muscle larval counts in the albendazole treated group were 93.5% and 90.6%, respectively. Moreover, Huang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most drugs that are used for treatment of Trichinella infection have low bioavailability and a high degree of resistance (Abd El-Hamed et al, 2022). That's why the recent research focus on the investigation of naturally originated medications for treatment of trichinellosis (Salama et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Trichinellosis is a perilous zoonotic parasitic disease of public health importance (Abd-ELrahman et al, 2020). Worldwide, approximately 11 million individuals and over 150 mammalian species as well as birds and reptiles have been infected by T. spiralis (Salama et al, 2021). Trichinella spiralis is present in Egypt, and it was diagnosed in man as well as in pigs slaughtered in Cairo abattoirs (Fahmy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%